2016
DOI: 10.1080/00207543.2016.1198506
|View full text |Cite
|
Sign up to set email alerts
|

Robust production planning and control for multi-stage systems with flexible final assembly lines

Abstract: Production planning of final assembly systems is a challenging task, as the often fluctuating order volumes require flexible solutions. Besides, the calculated plans need to be robust against the process-level disturbances and stochastic nature of some parameters like manual processing times or machine availability. In the paper, a simulation-based optimisation method is proposed that utilises lower level shop floor data to calculate robust production plans for final assembly lines of a flexible, multi-stage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The availability of an FMS can be defined as the ability of the manufacturing system to meet production demands in accordance with specified conditions and time interval [16]. Therefore, the availability of FMS depends on the relation between the output performance and the desired level of this performance-demand, which is determined outside the system.…”
Section: Availability Analysis Of the Fmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of an FMS can be defined as the ability of the manufacturing system to meet production demands in accordance with specified conditions and time interval [16]. Therefore, the availability of FMS depends on the relation between the output performance and the desired level of this performance-demand, which is determined outside the system.…”
Section: Availability Analysis Of the Fmsmentioning
confidence: 99%
“…Jain and Raj [15] performed three different approaches to analyze the intensity of performance variables in an organization and proposed the FMS performance index to intensify the factors, which affect FMS. In a multistage production system, Gyulai et al [16] proposed a simulation-based optimization method that utilizes lower-level shop floor data to calculate robust production plans for final assembly lines of a flexible, multistage production system. Rybicka, J. et al [17] demonstrated how discrete event simulation (DES) can address complexity in an FMS to optimize the production line performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focus on robust balancing of classic ALs (Moreira et al , 2015; Chica et al , 2016), while others focus on robust U-shaped AL balancing (Bagher et al , 2011) considering uncertainty in factors such as task times and demand. Gyulai et al (2017) proposed a robust SO approach for production planning of final ALs in a multi-stage production system considering stochasticity in processing times and machine availability. In a similar context, Gyulai et al (2015) combined regression modelling, mathematical programming and simulation analysis to obtain robust production planning and capacity control in flexible ALs with the objective of minimization of a cost function.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the industry of this study, the Production Planning and Control department (PPC), along with the Manufacturing Engineering act in the improving and management of the production. Studies show the lead-time for the manufacturing of the products is one of the most important parameters used by the PPC (Gyulai et al, 2017). There is also manufacturing capacity operation, inventory reduction and delivery time (Reschke and Schuh, 2017).The authors do not know the environmental impact parameters generated by the manufacturing technology, material or processes.…”
Section: Introductionmentioning
confidence: 99%